Estrategias lúdicas en el desarrollo del lenguaje verbal en niños de 4 años de la Unidad Educativa Carlos Cisneros - Lema González, Margoth Eulalia (2025)
The current work proposed analyzing the incidence of playful strategies for developing verbal language in 4-year-old children. It was necessary to analyze previous works to achieve the research's goal through a bibliographic review of books, brochures, theses, and scientific articles. It is quantitative research that uses a quasi-experimental design. It includes a descriptive, documentary, field, and transversal typology with an application level. Everything is done through a theoretical deductive method since it allows the proposal to propose an observation sheet that measures verbal language development. Before applying this observation sheet, a guide of playful activities was designed to develop verbal language better. "Let's talk with Margoth" was used to produce verbal language. This proposal contains 10 exercises designed for children's daily routines. The researcher applied this guide to the experimental group of the research to later apply the data collection instrument. Consequently, it was possible to gather the following data: in never, the control group had 11.40% while the experimental group had 8.60%. In almost never, the control group had 17% while the experimental group had 12.20%; sometimes, the control group had 36.20%. On the contrary, the experimental group had 30.60%, the control group had 34.60%, and the experimental group had 48.50%. Based on this data, it was possible to verify the hypothesis through the difference of proportions statistic, where a value of 1.72 is obtained, being more significant than the Zt, accepting the research hypothesis. Thus, Playful strategies help the development of verbal language in 4-year-old children of the Unidad Educativa Carlos Cisneros.